2002
DOI: 10.1046/j.1365-2958.2002.02724.x
|View full text |Cite
|
Sign up to set email alerts
|

The yeast transcriptome in aerobic and hypoxic conditions: effects of hap1, rox1, rox3 and srb10 deletions

Abstract: SummaryThe transcriptome of Saccharomyces cerevisiae was screened using the high-density membrane hybridization method, under aerobic and hypoxic conditions, in wild-type and mutant backgrounds obtained by the disruption of the genes encoding the regulatory proteins Hap1, Rox1 and the Srb10 and Rox3 subunits of RNA polymerase II holoenzyme. None of the mutations studied was able to fully overcome the wild-type hypoxic response. Deletion of the hap1 gene changed the expression profiles of individual open readin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
17
1

Year Published

2002
2002
2017
2017

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 78 publications
(19 citation statements)
references
References 42 publications
(43 reference statements)
1
17
1
Order By: Relevance
“…Under aerobic conditions, abundant heme activates the HAP1 complex that in turn transactivates the ROX1 gene. ROX1 protein blocks expression of a large set of hypoxia-responsive genes (Becerra et al, 2002). Under hypoxic conditions, heme-deficient HAP1 represses ROX1 transcription, and the hypoxia-responsive genes are derepressed (Zitomer et al, 1997).…”
Section: Mechanisms Of Gene Regulation In Response To Hypoxiamentioning
confidence: 99%
“…Under aerobic conditions, abundant heme activates the HAP1 complex that in turn transactivates the ROX1 gene. ROX1 protein blocks expression of a large set of hypoxia-responsive genes (Becerra et al, 2002). Under hypoxic conditions, heme-deficient HAP1 represses ROX1 transcription, and the hypoxia-responsive genes are derepressed (Zitomer et al, 1997).…”
Section: Mechanisms Of Gene Regulation In Response To Hypoxiamentioning
confidence: 99%
“…This is exemplified by the enrichment of regulatory motifs in the consistently anaerobically induced transcripts (Table II). Clearly, regulation by known transcriptional regulators (relief of ROX1 repression and transcriptional activation by UPC2) (30,65,66) is not sufficient to account for the transcriptional response of all 65 genes that were consistently up-regulated under anaerobic conditions. Indeed, our study strongly suggests that at least a third factor, which recognizes an AAGGCAC motif, is involved in transcriptional regulation by oxygen availability.…”
Section: Dna Microarrays As a Diagnostic Tool For Biotechnology-amentioning
confidence: 99%
“…One way that cells cope with changing oxygen levels is by dramatically altering gene expression (Semenza 2011; Butler 2013; Ratcliffe 2013). In the yeast Saccharomyces cerevisiae , several microarray studies have found that the mRNA levels of hundreds of genes change in response to hypoxia (ter Linde et al 1999; Becerra et al 2002; Ter Linde and Steensma 2002; Kwast et al 2002; Lai et al 2005, 2006; Hickman and Winston 2007; Hickman et al 2011). As might be expected, some responsive genes participate in oxygen-dependent cellular processes, such as aerobic respiration and the biosynthesis of unsaturated fatty acids (UFAs), heme, and ergosterol (the yeast functional equivalent of cholesterol).…”
mentioning
confidence: 99%